Measurement of Employee Workload at the Loading Ramp Station Using the CVL (Cardiovascular Load) Method at PT. Socfindo Seunagan - Defrizan Pahlepi; Khairul Hadi (Jurnal Inotera, 2023)
PT. Socfindo is a company that has many employees, should pay more attention to how much workload is given to its employees so they can carry out their work optimally. Workload that can be measured on employees includes physical workload and mental workload. The measurement method used is the Cardiovascular Load (CVL) for physical workload. Cardiovascular load is a method to determine the level of work fatigue. Data collection for physical workload was carried out by measuring the pulse using the 10 pulse method, and determining the %CVL results. The average working heart rate/minute for employee A is 105 while employee B's average working heart rate/minute is 106, based on the results of the calculation analysis for %CVL between 34% - 36%, so that the risk of work fatigue occurs and is in the moderate category. It can be concluded that the workload of employees needs improvement so that work fatigue does not occur so there is no risk of injury to the employee's body parts.